Activation-dependent surface expression of gC1qR/p33 on human blood platelets - Peerschke, Ellinor I. B.; Murphy, Tara K.; Ghebrehiwet, Berhane (Thrombosis and Haemostasis, 2003)
GC1qR/p33 (gC1qR) is expressed by a variety of somatic and cultured cells, including blood platelets. It interacts with several cellular, viral, bacterial, and plasma proteins, suggesting a potential role in thrombosis, inflammation, and infection. Considerable controversy has surrounded the surface membrane localization of gC1qR, however, since its cDNA sequence does not predict a traditional membrane-anchoring domain, and bears a typical mitochondrial targeting sequence. The present study examined gC1qR expression on resting and activated human blood platelets using flow cytometry and confocal microscopy with two monoclonal antibodies, 74.5.2 and 60.11, directed against gC1qR C-terminal amino acids 204-218, and N-terminal amino acids 76-93, respectively. Unstimulated platelets reacted minimally with either antibody. In contrast, platelet activation with TRAP, epinephrine, or ADP produced markedly increased gC1qR expression as reflected by 74.5.2 binding but not 60.11 binding. Platelet activation was verified using PAC-1 and anti CD 62 antibodies. Whereas PAC-1 binding to activated platelets could be reversed following platelet incubation with PGE1, 74.5.2 binding remained unchanged, suggesting the sustained expression of gC1qR following platelet stimulation. The data further demonstrate that detection of cell surface gC1qR may be dependent on antibody specificity. The ability of gC1qR to bind proteins involved in complement, coagulation, and kinin systems, as well as viral and bacterial pathogens including S. aureus protein A, supports the hypothesis that gC1qR expressed on activated platelets may contribute directly to thrombosis, inflammation, and endovascular infections.
Keywords: gC1qR/p33; platelets